Pengaruh Strategi Konten Marketing dan Keterlibatan Influencer di Media Sosial Terhadap Keputusan Pembelian dengan Kepercayaan Konsumen Sebagai Variabel Intervening (Studi Kasus Pada Pengguna Lazada di Kalangan Mahasiswa Jurusan Manajemen Angkatan 2022 Universitas Putra Indonesia “YPTK” Padang) - Imanina Salsa Bilkisti; M. Afuan; Deni Saputra (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of content marketing strategies and influencer involvement on social media on purchase decisions, with consumer trust as an intervening variable among Management students of the 2022 cohort at Universitas Putra Indonesia “YPTK” Padang who use Lazada. The population consisted of 900 students, and 100 respondents were selected using probability sampling techniques. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results indicate that content marketing has a positive and significant effect on purchase decisions and consumer trust. In contrast, influencer involvement does not have a significant effect on purchase decisions or consumer trust. Furthermore, consumer trust does not significantly influence purchase decisions and is unable to mediate the relationship between content marketing and purchase decisions, nor between influencer involvement and purchase decisions.